2009
DOI: 10.2746/042516409x434099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ventriculectomy versus ventriculocordectomy on upper airway noise in draught horses with recurrent laryngeal neuropathy

Abstract: VCE is recommended as the preferred treatment for RLN in draught horses. Further studies are required to evaluate the longevity of the procedure's results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 16 publications
0
44
0
3
Order By: Relevance
“…), a complication reported to occur in up to 6.6% of horses with a laryngotomy left to heal by second intention (Cramp et al . ). However, as this complication reported during healing of wounds by second intention was not observed in any of the 180 horses included in the present study, the argument seems to be of minor significance ( Figs a–f ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), a complication reported to occur in up to 6.6% of horses with a laryngotomy left to heal by second intention (Cramp et al . ). However, as this complication reported during healing of wounds by second intention was not observed in any of the 180 horses included in the present study, the argument seems to be of minor significance ( Figs a–f ).…”
Section: Discussionmentioning
confidence: 97%
“…; Cramp et al . ). These experiences with both primary and second intention healing, as well as the classification of the wound as clean‐contaminated, have probably led to the common impression that primary closure of the laryngotomy incision will lead to infection and ‘increase morbidity unnecessarily’ (Ducharme ).…”
Section: Introductionmentioning
confidence: 97%
“…; Cramp et al . ). For LP, the same research group reported that inspiratory sound level improved significantly from laryngeal hemiplegia values, but did not return to baseline (preneurectomy state), however VEC was not performed concurrently in this study (Brown et al .…”
Section: Quantity and Quality Of Evidence Presentedmentioning
confidence: 97%
“…Ventriculocordectomy alone appears to yield a high rate of owner satisfaction in draught breeds (Cramp et al . ).…”
Section: Quantity and Quality Of Evidence Presentedmentioning
confidence: 99%
“…Until recently, little was known about the efficacy of ventriculectomy or ventriculocordectomy in draft horses, although a single study of draft horse owner satisfaction suggests that RLN can be treated successfully by unilateral ventriculectomy without prosthetic laryngoplasty (Bohanon et al 1990). We found that both bilateral ventriculectomy and ventriculocordectomy significantly reduce upper airway noise but that ventriculocordectomy was more effective than ventriculectomy (Cramp et al 2009b). Furthermore, the procedure had few postoperati-J.…”
Section: Draft Horses With Rlnmentioning
confidence: 99%